Cooperative MAC protocol based on network coding and space-time coding - Qian-bin CHEN; Jian LIU; Yong FENG; Lun TANG (Tongxin xuebao)
Aiming at the problems in wireless ad hoc networks,such as relays’ low efficiency caused by cooperation and difficult to meet the different QoS requirements,a co e MAC protocol was proposed based on the combination of network coding and space-time coding(NSTCMAC).Based on NSTCMAC protocol with the combination of Network coding and space-time coding techniques,a kind of cooperative MAC transmission mechanism that could distinguish the type of DATA packet was designed in order to meet the QoS requirements of different types of transm Further more,cooperative transmission mechanism and its performance were analyzed through Markov chain model.When transmitting the non-real-time(NR) packets,network coding was adopted to improve the efficiency of relay nodes; when transmitting the real-time(R) packets,randomized distributed space-time coding(R-DSTC)was used to enhance the reliability of transmission.Simulation results show that NSTCMAC protocol can meet different QoS requirements better,and solve the problem of relays’ low efficiency more effectively,when compared with legacy DCF、COOPMAC and CD-MAC protocol.